A Comparative Study of E-Technological Leadership Competencies of Male and Female Head Teacher at Secondary School Level - Malik, Muhammad Shafi; Tabassum, Farkhanda (Annals of Human and Social Sciences, 2023)
E-Technological leadership competencies have a great importance for educational leaders to cover all the challenges in this rapidly changing world especially in the field of education in Pakistan. e-leadership competencies of secondary school heads plays a vital role to handle the e-technological issues to run the secondary schools smoothly .This research was carried out to compare the e-technological competencies of male and female head teachers at secondary school level. 21 female and 25 male head teachers were selected as a sample for this research study, data was collected through questionnaire from targeted sample. Data was analyzed using SPSS statistical tool, major findings of this research were concluded that the level of competencies of most of the male and female secondary school heads had high level of e- technological competencies in some areas including use of whatsApp group, printing of documents and use of e-mails. there was also a low level of competencies was identified in some areas , like conducting online meeting, use of multimedia and solving technical problems. There was no significant statistical difference seen between male and female secondary school heads in e-technological competencies This study recommends that use of e-technology is the key factor for both male and female head teachers in the field of e-leadership. Therefore, a comprehensive school leadership development training programs may be launched to enhance the e-technological leadership competencies of male and female head teachers at secondary schools level.